The Effect of Problem Based Learning Strategic and Divergent Thinking Style on The Ability to Solve Environmental The Problems (an Experimental Study at SMP Negeri 161 Jakarta, 2015) - Saurmaida Gultom (Universitas Negeri Jakarta, 2016)
The aim of the research is to identify the influence of learning strategic and divergent thinking style on the ability to solve the problems in environmental topic biology subject matter. This research was conducted in SMP Negeri 161 Jakarta. Experimental method with factorial 2 x 2 was applied on this research. The sampling objects were 60-second grade students. The two ways Varian analysis (ANAVA) was used in hypothesis test and continued by t-Dunnet test. The research conclusion were: 1) Generally, the students who used discussion problem learning strategy had better ability to solve the problem in environmental topic biology subject matter than students who used lecture problem learning strategy. 2) Generally there is significant difference ability to solve the problems in environmental topic biology subject matter between the students that had difference in divergent thinking style, the students with high divergent thinking style better than students with lower divergent thinking style 3) For the students with high divergent thinking style, used the discussion problem learning strategy had better the ability to solve the problems in environmental topic biology subject matter than the students that used lecture problem learning strategy. 4) For the students with lower divergent thinking style, used the lecture problem learning strategy had better the ability to solve the problems in environmental topic biology subject matter than the students that used discussion problem learning strategy. 5) There is significant interaction between learning strategy and divergent thinking style influence on the ability to solve the problems in environmental topic biology subject matter.